2008
DOI: 10.1021/nl801316d
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Production of a New Form of sp2 Carbon: Crystalline Graphene Nanoribbons

Abstract: We report the use of chemical vapor deposition (CVD) for the bulk production (grams per day) of long, thin, and highly crystalline graphene ribbons (<20-30 microm in length) exhibiting widths of 20-300 nm and small thicknesses (2-40 layers). These layers usually exhibit perfect ABAB... stacking as in graphite crystals. The structure of the ribbons has been carefully characterized by several techniques and the electronic transport and gas adsorption properties have been measured. With this material available to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
352
0
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 596 publications
(376 citation statements)
references
References 24 publications
17
352
0
7
Order By: Relevance
“…On comparing with the literature data on GNRs with similar dimensions, these values are close to that reported for GNRs produced via sonochemical unzipping of CNTs 10 and are significantly lower than that for lithography and other GNR production techniques ( Fig. 3g) [1][2][3]34 .…”
Section: Exfoliationsupporting
confidence: 86%
See 1 more Smart Citation
“…On comparing with the literature data on GNRs with similar dimensions, these values are close to that reported for GNRs produced via sonochemical unzipping of CNTs 10 and are significantly lower than that for lithography and other GNR production techniques ( Fig. 3g) [1][2][3]34 .…”
Section: Exfoliationsupporting
confidence: 86%
“…T he shape/size dependent quantum confinement in graphene nanostructures (GNs) control their electrical [1][2][3] , magnetic and optical properties [4][5][6][7][8][9] . Several studies have indicated that GNs with controlled structure can be incorporated into a wide variety of applications in electronics, optoelectronics and electromagnetics.…”
mentioning
confidence: 99%
“…[ 23 ] However the formation of graphite nanoribbons by the decomposition of CO/H 2 /Fe(CO) 5 at 400-700 ° C was reported in 1990. [ 24 ] Alternative chemical routes, consisting of the exfoliation of commercial graphite, [ 25 ] or by organic chemistry approaches, have also been recently developed ( Figure 4 ).…”
Section: Graphene Nanoribbonsmentioning
confidence: 99%
“…[ 30 ] Figure 4 . (a) and (b) SEM images of graphitic nanoribbons produced by CVD; [ 23 ] (c) AFM image of chemically derived nanoribbons from graphite (scale bars = 100 nm), [ 25 ] and (d) low magnifi cation TEM image of the nanoribbons produced by the ZnS template method. [ 26 ] (Adapted with permissions from American Chemical Society and American Association for the Advancement of Science).…”
Section: Graphene Nanoribbonsmentioning
confidence: 99%
“…[25][26][27][28][29] In singlehydrogen-terminated armchair ribbons, however, this phenomena is absent. Despite the broad range of production techniques for graphene ribbons 10,11,17,[30][31][32][33][34][35][36][37][38][39][40][41] real control over the edge geometry and termination in them has not been achieved yet, and no atomic characterization either.…”
Section: Introductionmentioning
confidence: 99%